A sea of miracles: Reflections on narrative space in medieval Serbian hagiography - Savić Aleksandar Z. (Zbornik Radova Vizantološkog Instituta, 2021)
The broad purpose of this essay is to demonstrate how scholarly readings of medieval hagiography might benefit from a theoretical-methodological shift towards space as the principal focal point of analysis. More specifically, it aims to put forward a new, spatial interpretation of two well-known miracle episodes from the Lives of St Sava of Serbia, both of which are said to have transpired on the high seas.